1987
DOI: 10.1139/f87-338
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Dynamics of Destabilized Chub (Coregonus spp.) Populations in Lakes Michigan and Huron, 1950–84

Abstract: Deepwater ciscoes (Coregonus spp.) or "chubs" of Lake Michigan far surpassed those of Lake Huron in yield, population density, and resilience following severe depletion in the 1960s and 1970s, when the bloater (C. hoyi) composed more than 90% of the stocks. The population decline of bloaters in recent decades was mainly attributed to exploitation, to the depression of chub recruitment (e.g. from inferred predation on early life stages) by nonendemic alewives (Alosa pseudoharengus) and rainbow smelt (Osmerus mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…We know of no genetic evidence of inbreeding within the Lake Michigan bloater population, however. A second potential mechanism is too few males limiting the number of eggs that are actually fertilized during periods of female predominance (Brown et al 1987). Using GLSC Lake Michigan bloater data through 1984, when the adult population was about 60% female, Brown et al (1987) predicted that female predominance would continue to rise and bloater recruitment would ultimately decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know of no genetic evidence of inbreeding within the Lake Michigan bloater population, however. A second potential mechanism is too few males limiting the number of eggs that are actually fertilized during periods of female predominance (Brown et al 1987). Using GLSC Lake Michigan bloater data through 1984, when the adult population was about 60% female, Brown et al (1987) predicted that female predominance would continue to rise and bloater recruitment would ultimately decline.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cold temperatures during winter and spring have been hypothesized to reduce bloater recruitment by lengthening the period of egg development and reducing the growth rates of bloater larvae, which in turn increases susceptibility to predators (Rice et al 1987). With regard to intrinsic factors, female predominance among adults has been hypothesized to limit recruitment and regulate bloater population size (Brown et al 1987). For other species such as Atlantic cod, recent studies have found maternal condition to influence the fecundity (Kjesbu et al 1991), egg quality (Ouellet et al 2001), and even recruitment to age 3 (Marshall et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Since the closure of the commercial fishery in Lake Michigan in 1976, increased density-dependent growth appears to be occurring (Jude and Tesar, 1985;Brown et al, 1987;Brown and Eck, 1992). Skewed sex ratios of bloater (e.g., 80-90% females) have been hypothesized to have contributed to the decline of bloater populations in lakes Michigan and Huron from ∼1960 until 1975 Crowder, 1980;Jude and Tesar, 1985;Brown et al, 1987). The mechanism by which the skewed sex ratios occur in bloater has been hypothesized to be the result of a change in the neuroendocrine aspect of bloaters or a reduced viability of males (Philips and Ehlinger, 1995;Turgeon et al, 1999).…”
Section: Intraspecific Competitorsmentioning
confidence: 99%
“…Brown et al (1987); Bunnell et al (2006) Condition-dependent fecundity: Reduced condition of adults has reduced size-dependent fecundity. Bunnell et al (2009) Climate: Cold winters could prolong egg incubation period and increase vulnerability of eggs to predators.…”
Section: Referencesmentioning
confidence: 99%